Sleep apnoea and unscheduled re-admission in patients undergoing coronary artery bypass surgery. Issue 1 (September 2015) - Zhao, Liang-Ping; Kofidis, Theodoros; Chan, Siew-Pang; Ong, Thun-How; Yeo, Tiong-Cheng; Tan, Huay-Cheem; Lee, Chi-Hang
Abstract Introduction Although it has been recognised as a cardiovascular risk factor, data on sleep apnoea screening before coronary artery bypass grafting (CABG) are scarce. This study sought to determine the prevalence, predictors and effects of sleep apnoea on re-admission in patients undergoing CABG. Method We prospectively recruited 152 patients to undergo an overnight sleep study before CABG. Sleep apnoea was defined as an apnoea-hypopnoea index of ≥15 events per hour. Data on unscheduled re-admission due to cardiovascular events were collected. Results Among the 138 patients who completed the sleep study, sleep apnoea was diagnosed in 69 (50%). The patients who had sleep apnoea had a lower left ventricular ejection fraction (p = 0.029), a larger left atrial diameter (p = 0.014) and a larger left ventricular end-systolic dimension (p = 0.019) than those who did not. Angiographic SYNTAX and Gensini scores were similar in patients with and without sleep apnoea. The generalised structural equation model revealed that hypertension, a high body mass index and chronic renal failure were independent predictors of sleep apnoea (p < 0.05). After an average follow-up of 6 ± 3 months, 12 patients with sleep apnoea (17.3%) and three patients without sleep apnoea (4.3%) were involved in unscheduled re-admission. Patients with sleep apnoea were almost five times more likely to have an unscheduled re-admission due to cardiovascular events (adjusted odds ratio: 4.63, 95% CI: 1.24–17.31, p = 0.023) than those without sleep apnoea. Conclusions Sleep apnoea was prevalent and predictive of unscheduled re-admissions in patients scheduled for CABG.